Metabolic Profiling of Aliphatic, hydroxy, and Methyl-Branched Fatty Acids in Human Plasma by Gas Chromatography–Mass Spectrometry. (13th April 2018) - Seo, Chan; Kim, Youngbae; Lee, Hyeon-Seong; Kim, Sook Za; Paik, Man-Jeong
ABSTRACT: An efficient method for the simultaneous profiling analysis of 44 fatty acids including 24 aliphatic, 12 hydroxyl, and eight methyl-branched fatty acids as tert -butyldimethylsilyl (TBDMS) derivatives was developed by gas chromatography–mass spectrometry. In this study, new mass spectral databases of isolauric, 11-methyllauric, isomyristic, isopentadecylic, isopalmitic, isostearic, 17-methylstearic, and 19-methylarachidic acids were constructed as TBDMS derivatives. Under the optimal conditions, linearity in the range of 0.1–10.0 µg/mL (24 aliphatic fatty acids) and 0.01–1.0 µg/mL (eight methyl-branched and 12 hydroxy fatty acids) showed good correlation coefficients ( r  ≥ 0.997). The repeatability showed relative standard deviation of less than 11.2% and accuracy (percent relative error) varied from −11.0 to 7.8 for the 44 fatty acids studied. The recoveries ranged from 61.7 to 90.1% with good repeatability. When applied to human plasma sample, 18 aliphatic, three 2-hydroxy, three 3-hydroxy, and five methyl-branched fatty acids were positively identified and quantified. Therefore, the present method will be useful for profiling analysis of various fatty acids in biological samples including plasma.